Ovivo to provide water treatment equipment for North Sea oil platform. Issue 10 (October 2015) - Unknown
Abstract : Ovivo Inc has been awarded a C8 million contract to design and supply modular fresh water makers for an offshore oil production platform located in the North Sea.